Creation of a 3D printed human head phantom (Transactions on Additive Manufacturing Meets Medicine, 2021)
Deep brain stimulation (DBS) is a neurological intervention to treat neurological diseases such as Parkinson’s disease. The postoperative position determination of the electrode is critical to determine if the surgery was successful. This study aimed to develop a human head phantom by using additive manufacturing (AM). With these phantom new findings in postoperative position determination on computed tomography images can be gained. Necessary to that end, the head phantom should be as anatomically correct as possible. Furthermore, the brain and the bones should be represented with realistic CT values on computed tomography (CT) images. The first measurements showed that the CT values of the 3D printed skull correspond to the CT values of the human skull and the CT values of the phantom’s brain are equivalent to values slightly above these of the human brain.
Keywords: 3D printing; human phantom; phantom; additive manufacturing; deep brain stimulation